Scientific Realism in Particle Physics : a Causal Approach. - Egg, Matthias (Deutsche Hochschulschriften. Epistemische Studien., 2014)
Does particle physics really describe the basic constituents of the material world or is it just a useful tool for deriving empirical predictions? This book proposes a novel answer to that question, emphasizing the importance of causal reasoning for the justification of scientific claims. It thereby responds to general worries about scientific realism as well as to more specific challenges stemming from the interpretation of quantum physics.